Dynamics of oxylipin biosynthesis in systemic inflammation: insights from a large animal model of endotoxemia - Myers, Madison N.; Chirivi, Miguel; dos Santos Neto, Jose M.; Parales-Girón, Jair; Worden, Lynn C.; Lock, Adam L.; Contreras, G. Andres (Frontiers in Immunology, 2025)
IntroductionEndotoxemia, marked by the presence of bacterial lipopolysaccharide (LPS) in the bloodstream, induces acute inflammation and is implicated in both mortality and chronic disease across species. LPS stimulates lipolysis and activates cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP450) enzymes, promoting the synthesis of bioactive lipid mediators known as oxylipins (OXL). However, the dynamics of OXL production during systemic inflammation remain poorly defined, particularly in large animals.MethodsTo investigate OXL responses to endotoxemia, mature Holstein cows were administered intravenous infusions of either LPS or sterile saline (SAL). Plasma samples were collected at baseline (PRE), 2 hours post-infusion (+2H), and 12 hours post-infusion (+12H). OXL profiles were quantified using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Complementary in vitro experiments were conducted using bovine adipocytes exposed to LPS to assess adipocyte-specific OXL release.ResultsLPS-treated cows exhibited classical signs of endotoxemia, including tachycardia, fever, and tachypnea. Plasma OXL profiling revealed significant alterations in arachidonic acid (AA)- and eicosapentaenoic acid (EPA)-derived pathways. Notably, LPS infusion led to persistent increases in COX- and LOX-derived pro-inflammatory OXL, including thromboxane B₂ and hydroxyeicosatetraenoic acids (HETEs), alongside transient elevations in EPA- and docosahexaenoic acid (DHA)-derived pro-resolving mediators. In vitro, LPS stimulation of adipocytes increased the release of AA-based 5-HETE, 6-keto-PGF₁α, linoleic acid (LA)-based 13-HODE, and DHA-based 19,20-DiHDPA.DiscussionThese findings indicate that LPS induces robust activation of pro-inflammatory OXL pathways with limited and transient engagement of pro-resolving lipid mediators. The imbalance may contribute to sustained or dysregulated inflammation. Our study provides novel insights into both systemic and adipocyte-specific OXL dynamics during endotoxemia and highlights their potential as biomarkers and therapeutic targets for modulating inflammation.